ChemInform Abstract: Synthesis of Manganese Dioxide/Iron Oxide/Graphene Oxide Magnetic Nanocomposites for Hexavalent Chromium Removal. Issue 38 (3rd September 2015) - Liu, Yan; Luo, Chao; Cui, Guijia; Yan, Shiqiang
Abstract MnO2/Fe3O4/graphene oxide (GO) and MnO2/Fe3O4/graphene nanocomposites are prepared by a two‐step reaction involving solvothermal reaction of an ultrasonicated dispersion of graphene oxide and Fe(acac)3 in ethylene glycol with and without the addition of N2H4 hydrate (autoclave, 180 °C, 16 h) followed by MnO2 coating in an KMnO4 aqueous solution (circulator, 80 °C, 3 h, pH 5 and pH 2).